Isolation of a New RNA Polymerase-Binding Protein from Sporulating Bacillus subtilis - Greenleaf, Arno L. (National Academy of Sciences, 1973)
RNA polymerase was precipitated from extracts of radioactively labeled vegetative and sporulating Bacillus subtilis with antiserum prepared against vegetative core polymerase. The precipitates were solubilized and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Antiserum added to an extract of vegetative B. subtilis precipitated only the known subunits of core RNA polymerase, but antiserum added to an extract of sporulating cells precipitated a new polypeptide of 70,000 daltons in addition to the subunits of core enzyme. The 70,000-dalton polypeptide precipitated from an extract of a mixture of vegetative and sporulating B. subtilis, separately labeled with two different radioisotopes, contained only the radioisotope characteristic of the sporulating cells. The 70,000-dalton protein has been freed of core RNA polymerase and extensively purified by chromatography on phosphocellulose. Precipitation of the purified 70,000-dalton protein by the anti-polymerase serum requires the prior addition of vegetative or sporulation core RNA polymerase. The reaction is specific since the purified protein is not precipitated during antibody precipitation of either phage λ repressor or bovine serum albumin. The RNA polymerase-binding protein appears during the third hour of sporulation and is apparently not synthesized by the sporulation-defective mutant rfr 10.